Oxygen and sulfur isotope systematics of sulfate produced by bacterial and abiotic oxidation of pyrite - Balci, Nurgul; Shanks, Wayne C.; Mayer, Bernhard; Mandernack, Kevin W. (Elsevier BV, 2007)
Abstract To better understand reaction pathways of pyrite oxidation and biogeochemical controls on δ18O and δ34S values of the generated sulfate in acid mine drainage (AMD) and other natural environments, we conducted a series of pyrite oxidation experiments in the laboratory. Our biological and abiotic experiments were conducted under aerobic conditions by using O2 as an oxidizing agent and under anaerobic conditions by using dissolved Fe(III)aq as an oxidant with varying δ18OH2O values in the presence and absence of Acidithiobacillus ferrooxidans. In addition, aerobic biological experiments were designed as short- and long-term experiments where the final pH was controlled at ∼2.7 and 2.2, respectively. Due to the slower kinetics of abiotic sulfide oxidation, the aerobic abiotic experiments were only conducted as long term with a final pH of ∼2.7. The δ34SSO4 values from both the biological and abiotic anaerobic experiments indicated a small but significant sulfur isotope fractionation (∼−0.7‰) in contrast to no significant fractionation observed from any of the aerobic experiments. Relative percentages of the incorporation of water-derived oxygen and dissolved oxygen (O2) to sulfate were estimated, in addition to the oxygen isotope fractionation between sulfate and water, and dissolved oxygen. As expected, during the biological and abiotic anaerobic experiments all of the sulfate oxygen was derived from water. The percentage incorporation of water-derived oxygen into sulfate during the oxidation experiments by O2 varied with longer incubation and lower pH, but not due to the presence or absence of bacteria. These percentages were estimated as 85%, 92% and 87% from the short-term biological, long-term biological and abiotic control experiments, respectively. An oxygen isotope fractionation effect between sulfate and water ( e 18 O SO 4 – H 2 O ) of ∼3.5‰ was determined for the anaerobic (biological and abiotic) experiments. This measured e 18 O SO 4 2 - – H 2 O value was then used to estimate the oxygen isotope fractionation effects ( e 18 O SO 4 2 - – O 2 ) between sulfate and dissolved oxygen in the aerobic experiments which were −10.0‰, −10.8‰, and −9.8‰ for the short-term biological, long-term biological and abiotic control experiments, respectively. Based on the similarity between δ18OSO4 values in the biological and abiotic experiments, it is suggested that δ18OSO4 values cannot be used to distinguish biological and abiotic mechanisms of pyrite oxidation. The results presented here suggest that Fe(III)aq is the primary oxidant for pyrite at pH